Mid-term outcomes of a partial 2-stage approach in late chronic periprosthetic hip infections. Issue 3 (May 2020) - Castagnini, Francesco; Tella, Giuseppe; Montalti, Maurizio; Biondi, Federico; Bordini, Barbara; Busanelli, Luca; Toni, Aldo
Introduction: Late chronic periprosthetic infections (LCPIs) are worrisome complications of primary hip arthroplasties. The gold standard procedure is the 2-stage revision. 1-stage exchange is gaining popularity in order to reduce the invasivity of the former technique. A partial 2-stage exchange technique, retaining fixed components, may overcome some of the drawbacks of the previous techniques, allowing a much easier reconstruction step. Methods: 28 patients with a LCPI after a primary total hip arthroplasty underwent a first removal stage: the loosened component was removed (23 cups and 5 stems) and the fixed component, with no local signs of infection, was retained. An antibiotic hand molded spacer was positioned in 16 cases. After a mean time of 8 months and a tailored antimicrobial therapy, the spacer was removed and the implant was revised. Results: The mean follow-up was 5 years. The HHS score was 82.7. 4 cases failed (2 patients presenting a septic relapse after revision and 2 patients undergoing Girdlestone arthroplasty), achieving a survival rate of 83.4% at 5 years. 2 patients were unwilling to perform a further procedure and did not proceed to the second stage. All the other patients had no clinical, radiological, laboratory signs of septic relapse. Conclusions: The partial 2-stage approach seems a promising technique for LCPI in selected cases, with good infection control. It allows an easier revision by sparing the fixed components. Larger case series and longer follow-ups are needed to confirm the results and identify the limits of this approach.